RGD-conjugated rod-like viral nanoparticles on 2D scaffold improve bone differentiation of mesenchymal stem cells - Sitasuwan, Pongkwan; Lee, L. Andrew; Li, Kai; Nguyen, Huong Giang; Wang, Qian (Frontiers in Chemistry, 2014)
Viral nanoparticles have uniform and well-defined nano-structures and can be produced in large quantities. Several plant viral nanoparticles have been tested in biomedical applications due to the lack of mammalian cell infectivity. We are particularly interested in using Tobacco mosaic virus (TMV), which has been demonstrated to enhance bone tissue regeneration, as a tuneable nanoscale building block for biomaterials development. Unmodified TMV particles have been shown to accelerate osteogenic differentiation of adult stem cells by synergistically upregulating BMP2 and IBSP expression with dexamethasone. However, the lack of affinity to mammalian cell surface resulted in low initial cell adhesion. In this study, to increase cell binding capacity of TMV based material the chemical functionalization of TMV with arginine-glycine-aspartic acid (RGD) peptide was explored. An azide-derivatized RGD peptide was “clicked” to tyrosine residues on TMV outer surface via an efficient copper(I) catalysed azide-alkyne cycloaddition reaction. The ligand spacing is calculated to be 2-4 nm, which could offer a polyvalent ligand clustering effect for enhanced cell receptor signalling, further promoting the proliferation and osteogenic differentiation of bone marrow derived mesenchymal stem cells.